'Still Steel' Urban Patterns - Sofokleous, Konstantina (My University, 2025)
Integrating steel patterns and motifs photographed and archived over two decades from both old and modernist houses in Cyprus, this AI-Project engages urban memory with flora, fauna, and archaeological materiality.
Keywords: AI Art, Digital Heritage